(untitled) (Jurnal Bakti Masyarakat Indonesia, 2024)
Waste is an environmental issue that needs to be taken seriously. In Cirebon Regency, waste production is so abundant that it is predicted that landfills will run out of space by 2025. Therefore, a village-based waste management is needed to solve this problem. The existence of waste in the environment, especially household waste, needs to be addressed with sustainable waste management by processing waste at the household level. The aim of this community service activity is to empower the village assets in increasing community knowledge about waste management and providing training to the community through processing household waste into eco enzymes which have many beneficial values. This service activity was carried out in Klangenan Village, Cirebon Regency, West Java. The method used was the ABCD (Asset-Based Community Development) approach. The results of this service activity are: (1) the community began to realize the importance of managing and processing waste independently, (2) the community has knowledge and ability regarding techniques for processing waste into more valuable products in a sustainable manner, and (3) the community began to actively play a role in solving the waste problem in Klangenan Village so as to create a clean, comfortable and healthier environment. This community service in Klangenan Village is expected to initiate other similar activities, such as cleaning up the river, training to make products from plastic waste, or processing organic waste into fertilizer for household gardens ABSTRAK: Sampah merupakan masalah lingkungan yang perlu ditangani secara serius. Di Kabupaten Cirebon produksi sampah sangat melimpah sehingga diprediksi Tempat Pembuangan Akhir (TPA) tidak mampu lagi menampung sampah pada tahun 2025. Oleh karena itu, pengelolaan sampah berbasis desa sangat diperlukan untuk mengatasi hal ini. Keberadaan sampah di lingkungan khususnya sampah rumah tangga juga perlu disikapi dengan pengelolaan sampah yang berkelanjutan dengan melakukan pengolahan sampah pada level rumah tangga. Tujuan dari kegiatan pengabdian masyarakat ini adalah untuk pemberdayaan aset-aset desa dalam meningkatkan pengetahuan masyarakat tentang pengelolaan sampah dan memberikan pelatihan kepada masyarakat melalui pengolahan sampah rumah tangga menjadi eco enzyme yang mempunyai banyak nilai manfaat. Kegiatan pengabdian ini dilakukan di Desa Klangenan Kabupaten Cirebon, Jawa Barat. Metode yang digunakan yakni pendekatan ABCD (Asset-Based Community Development). Hasil dari kegiatan pengabdian ini yaitu: (1) masyarakat mulai menyadari akan pentingnya pengelolaan dan pengolahan sampah secara mandiri, (2) masyarakat memiliki pengetahuan dan kemampuan tentang teknik pengolahan sampah menjadi produk yang lebih bernilai secara berkelanjutan, dan (3) masyarakat mulai secara aktif berperan dalam memecahkan masalah sampah di Desa Klangenan sehingga tercipta suatu lingkungan yang bersih, nyaman, dan lebih sehat. Pengabdian kepada Masyarakat di Desa Klangenan ini diharapkan dapat menginisiasi kegiatan-kegiatan serupa lainnya, seperti pembersihan sampah di sungai, pelatihan pembuatan produk dari bahan sampah plastik, atau pengolahan sampah organik sebagai pupuk untuk kebun rumah tangga.